Learning physics through experiments: an approach to physics in the Misak Indigenous Reservation (Olhar de Professor, 2022)
This article analyzes the learning process of physics through the projects developed by the students of Secondary Education using the didactic laboratory.  The context where this study was carried out was the Misak Agricultural Educational Institution, located in the Municipality of Silvia in the Department of Cauca, Colombia.  The participants were eighteen Middle Education students between 15-17 years of age, who were organized into three groups.  The methodology used was qualitative descriptive, addressing data collection through observation of participants where recordings (video-audios), photos and field notebooks were used.  Participant observation is described by four stages: 1) planning, 2) development, 3) construction, and 4) socialization.  The results show that the use of the didactic laboratory promotes the appropriation of physics concepts through the development of projects, strengthening meaningful learning and generating relationships between ancestral knowledge, universal knowledge and prior knowledge of students.  Additionally, three projects developed by the students are presented, such as: the town mill, the chiva and the lamp, which denote culturally and traditionally representative objects in the Misak indigenous community.
Keywords: Physics. Learning. Experiment. Misak Indigenous Reservation. Didactic laboratory.